Slow Release Behavior Of Biodegradable Starch Polyvinyl Alcohol Urea Fertilizer - Lum, Yip Hing (2018)
By the year 2050,the world population will be projected to reach 9 billion.The world arable land areas are reported to decline in the past years with potentially disastrous consequences as global demand of food soars. There will be absolutely need that the use of nitrogen fertilizers as the primary vital nutrients in crop output must be increased.The most widely used is urea due to its high nitrogen content,46% by weight which has surpassed other nitrogen fertilizer.However,approximately 70% of the high soluble urea fertilizer may be lost into the environment through surface runoff,leaching,and volatilization,thereby reduce farmer’s profit and lead to serious environmental pollution.The slow release fertilizer is most often suggested to avoid losses of nitrogen from agricultural land.Nevertheless,the cost of producing slow release fertilizer has limited its development and accumulation of hydrophobic matrix is a menace to environment.The objective of this study were to examine the performance of synthesized biodegradable matrix based urea fertilizer compared to conventional urea fertilizer in relation to slow release properties, ammonium retention and ammonia loss under flooded condition.Tapioca starch was crosslinked with polyvinyl alcohol by using boric acid to form a matrix having slow release characteristic when immersed in water.The experiments were arranged in a two-level factorial design with three replications. Treatments were two levels of concentration of boric acid (-1: 1 %; +1: 4%),reaction time (-1: 1 hour; +1: 4 hours) and heating temperature (-1:60℃; +1: 90℃) in the synthesis formulation and condition of crosslinked matrix.The soil burial degradation data showed that synthesized matrix were still able to degrade in the range of 35.81% to 56.48% even in the presence of boric acid crosslinking.Compared to conventional urea fertilizer which was dissolved within seconds in water,the synthesized matrix slowly released the urea completely during the 8 hours soaking period at 30ºC with the rotation speed of 100 rpm.The release mechanism of the urea from the synthesized matrix obeyed the Korsmeyer-Peppas model with a quasi-Fickian diffusion mechanism.Soil incubation experiments showed that the matrix could retain the soil exchangeable ammonium due to partially negatively charged sites after ionization of matrix. Urea encapsulated with matrix significantly reduced ammonia loss from urea by 40% up to 55% compared with pure urea alone.Hence,there was a widely potential utility of matrix in agricultural industry as fertilizer carrier due to its simple step in manufacturing process,environmental friendly,and high nitrogen use efficiency.